Risk Factors for Anxiety in Housewives during the COVID-19 Pandemic - Sifa Latif Khasana; Yudhi Wibowo; Rahmawati Wulansari (Journal of Epidemiology and Public Health, 2022)
Background: The COVID-19 pandemic has a psychological impact on society, namely anxiety. Factors that influence anxiety during the COVID-19 pandemic are age, education level, occupation, and history of being diagnosed with COVID-19. This study aims to determine the risk factors for anxiety in housewives during the COVID-19 pandemic.Subjects dan Method: An observational analytic study with a cross-sectional approach was conducted in South Purwokerto, Central Java. The sample is 70 housewives selected by simple random sampling. The dependent variable is anxiety. independent variables were age, education, occupation, and COVID-19 infection. Anxiety was measured by the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. Other variables were collected by questionnaire. Data were analyzed using Chi-square.Results: Age 40 years (OR= 1.55; 95%CI= 0.76 to 3.14; p= 0.330), higher education level (OR= 1.96; 95%CI= 1.03 to 3.71; p= 0.070), informal occupation (OR= 1.24; 95%CI= 0.44 to 3.48; p= 1,000), and a history of COVID-19 infection (OR= 31.10; 95%CI= 4.44 to 217.91; p<0.001) increased anxiety among housewives.Conclusion: Age 40 years, higher education level, informal occupation, and history of COVID-19 infection increase anxiety among housewives during the COVID-19 pandemic. Keywords: COVID-19, housewife, anxiety Correspondence:Sifa Latif Khasana. Faculty of Medicine, Universitas Jenderal Soedirman. Jl. Dr. Gumbreg 1, Mersi, Purwokerto Kidul, Purwokerto 53147, Banyumas, Central Java. Email: sifalatifkhasana@gmail.com. Mobile: 085826669720.